CONCEPT OF ORNAMENTATION BASED ON LOCAL WISDOM IN PUBLIC BUILDINGS IN THE URBAN AREA OF TAKENGON - Mardhatillah, Rizqi; Idawati, Dyah Erti; Izziah, Izziah; Maharani, Lisa; Kh, Fithria Zahwa (Journal of Architecture&ENVIRONMENT, 2025)
The Gayonese, an ethnic group indigenous to the highland regions of Aceh, are distinguished by their rich cultural heritage. Their cultural patrimony is characterized by a diversity of artistic expressions, including ornamental designs that embody the community's local wisdom and cultural identity. Takengon, the most vibrant town in Aceh's highland region, is home to numerous public buildings, including governmental, religious, educational, hospitality, and other service facilities, which incorporate ornamental elements as expressions of local wisdom. However, the application of these ornaments varies significantly by placement, symbolism, and color due to the absence of standardized guidelines for their implementation in public architecture. The main objectives of this research are twofold. Firstly, to examine the prevailing patterns of ornamentation in public buildings from a semiotic perspective. Secondly, grouping in local wisdom to develop a comprehensive framework for the systematic integration of ornamentation within Takengon's architectural landscape. This research employs a qualitative approach with semiotic analysis to interpret the visual symbols and meanings of ornamentation in public buildings, aiming to reveal the cultural and symbolic values embedded within. The methods of data collection employed involve the observation of ten public buildings, documenting, and interviewing informants. The informants in this research were government officials, cultural or community leaders, building consultants, and academics. The findings reveal the placement of ornamentation typically occurs in three main zones: the head, body, and base of the building. In terms of ornament typology, natural motifs are predominant, surpassing geometric and floral patterns, with no representations of fauna identified among the ten sampled buildings. Ornamentation in Takengon's public buildings primarily serves a decorative purpose, classified as applied ornamentation, rather than fulfilling structural or constructive functions. The contribution of this research lies in its enrichment of the discourse on cultural identity in the built environment, particularly in relation to ornamentation.